Discrimination at Work: Comparing European, French, and American Law - Mercat-Bruns, Marie (University of California Press, 2016)
How do the United States and France differ in laws and attitudes concerning discrimination at work? Franco-American scholar Marie Mercat-Bruns interviews prominent legal scholars to demonstrate how these two post-industrial democracies have adopted divergent strategies. Whereas employers in the United States and France rarely discriminate openly, deep systemic discrimination exists in both countries, each with a unique history of dealing with difference. Powerful and incisive, the book examines hot-button issues such as racial and religious bias, sexual harassment, gender discrimination, and equality for LGBT individuals, highlighting comparisons that will further discussions on social equality and fundamental human rights across borders.